The Dialectics of Wayang in The Wali Songo’s Da'wah: Qur'an and Hadith Perspective - Kudhori, Muhammad; Purwaningsih, Sri; Maulidina, Karina Tri; Salama, Mayu Maulida (UIN Maulana Malik Ibrahim Malang, 2025)
After Ustadz Khalid Basalamah prohibited Wayang performances in one of his lectures, public debate intensified regarding their legal status in Islamic law. Although discussions on the legality of Wayang are not new and date back to the Wali Songo era, previous studies have rarely examined the specific jurisprudential reasoning that enabled the Wali Songo to employ Wayang as a medium of da'wah within the Syafi‘i framework. This study fills that gap by analyzing how the Wali Songo justified Wayang performance through the permissive opinion of al-Qasim ibn Muhammad ibn Abi Bakr, who allowed two-dimensional depictions of animate beings. However, over time, scholars negotiated this dialectic, enabling Wayang to be utilized as an effective medium of da'wah by the Wali Songo. This article investigates how the Wali Songo justified the use of Wayang as a da'wah medium despite the prohibitive stance of the Syafi‘i school. This study employs a qualitative library-research approach, using content analysis and descriptive-analytical methods. Evidence indicates that the Wali Songo likely adopted the opinion of al-Qasim ibn Muhammad ibn Abi Bakr, who allowed two-dimensional depictions of animate beings based on several prophetic traditions. Their position reflects a non-rigid, moderate approach that prioritizes broader public benefit (maslahah) when addressing communal issues, particularly in formulating effective da'wah strategies. These findings suggest that modern Islamic educators, artists, and preachers can draw upon the Wali Songo’s method as a model for integrating cultural media with Islamic ethics—emphasizing moderation, creativity, and contextual wisdom in delivering religious messages. Future research should undertake comparative jurisprudence by examining the arguments of al-Qasim ibn Muhammad ibn Abi Bakr alongside other Sunni legal schools to further justify the Wali Songo’s reasoning. Such studies may also explore the application of maslahah in the use of contemporary media as tools for Islamic da'wah.Setelah Ustadz Khalid Basalamah melarang pertunjukan Wayang dalam salah satu ceramahnya, perdebatan publik semakin menguat mengenai status hukumnya dalam pandangan syariat Islam. Meskipun diskusi tentang legalitas Wayang bukanlah hal baru dan telah muncul sejak masa Wali Songo, penelitian-penelitian sebelumnya jarang menelaah secara spesifik dasar pertimbangan fikih yang memungkinkan Wali Songo menggunakan Wayang sebagai media dakwah dalam kerangka mazhab Syafi‘i. Penelitian ini mengisi kesenjangan tersebut dengan menganalisis bagaimana Wali Songo membenarkan penggunaan Wayang melalui pandangan permisif al-Qasim ibn Muhammad ibn Abi Bakr, yang memperbolehkan penggambaran makhluk hidup dalam bentuk dua dimensi. Seiring waktu, para ulama menegosiasikan dialektika ini, sehingga Wayang dapat dimanfaatkan secara efektif sebagai sarana dakwah oleh Wali Songo. Artikel ini menelusuri bagaimana Wali Songo membenarkan penggunaan Wayang sebagai media dakwah meskipun terdapat larangan ketat dalam mazhab Syafi‘i. Penelitian ini menggunakan pendekatan kualitatif berbasis kepustakaan dengan metode analisis isi dan deskriptif-analitis. Temuan menunjukkan bahwa Wali Songo kemungkinan besar mengadopsi pendapat al-Qasim ibn Muhammad ibn Abi Bakr yang memperbolehkan gambar dua dimensi makhluk hidup berdasarkan beberapa hadis Nabi. Pendekatan mereka mencerminkan sikap moderat dan tidak kaku yang mengutamakan kemaslahatan umum (maslahah) dalam menyelesaikan persoalan keagamaan, khususnya dalam merumuskan strategi dakwah yang efektif. Hasil penelitian ini menunjukkan bahwa para pendidik, seniman, dan dai Muslim modern dapat meneladani metode Wali Songo sebagai model integrasi antara media budaya dan etika Islam—dengan menekankan moderasi, kreativitas, dan kearifan kontekstual dalam menyampaikan pesan keagamaan. Penelitian selanjutnya disarankan melakukan kajian perbandingan hukum Islam dengan menelaah argumen al-Qasim ibn Muhammad ibn Abi Bakr bersama mazhab-mazhab Sunni lainnya untuk memperkuat justifikasi rasional Wali Songo. Kajian lanjutan juga dapat mengeksplorasi penerapan prinsip maslahah dalam penggunaan media kontemporer sebagai sarana dakwah Islam.